2020
DOI: 10.26434/chemrxiv.13171634.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Dynamic Substrate is Required for MhuD-catalyzed Degradation of Heme to Mycobilin

Abstract: The non-canoncial heme oxygenase MhuD from <i>Mycobacterium tuberculosis</i> binds a heme substrate that adopts a dynamic equilibrium between planar and out-of-plane ruffled conformations. MhuD degrades this substrate to an unusual mycobilin product via successive monooxygenation and dioxygenation reactions. This article establishes a causal relationship between heme substrate dynamics and MhuD-catalyzed heme degradation resulting in a revised enzymatic mechanism. UV/Vis absorption (Abs) and electr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…30 Kinetic analysis is complicated by the fact that IsdG intermediates and products absorb light at this wavelength, 16 but these issues have been addressed in a recently reported analytical expression. 13 Based upon the data reported here (Figure 7), and the kinetic model reported previously, WT IsdG monooxygenates heme with a pseudo-first order rate constant of 0.111 ± 0.004 min -1 . Upon introduction of the W67F substitution, the rate decreases to 0.049 ± 0.006 min -1 .…”
Section: Figuresupporting
confidence: 78%
See 4 more Smart Citations
“…30 Kinetic analysis is complicated by the fact that IsdG intermediates and products absorb light at this wavelength, 16 but these issues have been addressed in a recently reported analytical expression. 13 Based upon the data reported here (Figure 7), and the kinetic model reported previously, WT IsdG monooxygenates heme with a pseudo-first order rate constant of 0.111 ± 0.004 min -1 . Upon introduction of the W67F substitution, the rate decreases to 0.049 ± 0.006 min -1 .…”
Section: Figuresupporting
confidence: 78%
“…14 However, a recent in proteo MS study of the non-canonical HO MhuD revealed that the product isolation approach can fail to detect alternate enzyme products. 13 Indeed, ESI-MS of the WT IsdG reaction mixture 60 min after the addition of ascorbate reveals a mixture of m/z 583, 599, and 611 species (Figure 8). The 599 and 611 Da species were previously observed for IsdG-catalyzed heme degradation, 16 and attributed to the staphylobilin product and formyloxobilin intermediate, respectively.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations